Pengaruh Beasiswa KIP-Kuliah Terhadap Prestasi Belajar Mahasiswa Jurusan Pendidikan Ekonomi - Nurnaningsih Halid; Meyko Panigoro; Ardiansyah Ardiansyah; Roy Hasiru; Abdulrahim Maruwae (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to examine the influence of the KIP-Kuliah (Smart Indonesia Card for College) Scholarship on the academic performance of students in the 2021 cohort of the Department of Economics Education at the Faculty of Economics and Business, Universitas Negeri Gorontalo. The research adopts a quantitative approach with an explanatory research method. Primary data were collected through the distribution of questionnaires, with a sample size of 32 respondents. Data analysis was conducted using simple linear regression. The findings indicate that the KIP-Kuliah Scholarship significantly influences students' academic performance in the Department of Economics Education, 2021 cohort. The scholarship's contribution to students' academic achievement is 46.9%, while the remaining 53.1% is attributed to other variables not examined in this study.